Engraftment of self-renewing endometrial epithelial organoids promotes endometrial regeneration by differentiating into functional glands in rats - Ma, Yana; Qian, Jingjing; Xu, Xin; Wei, Cheng; Wang, Minyuan; Zhang, Peipei; Chen, Sijia; Zhang, Lingyan; Zhang, Yanling; Wang, Yanpeng; Xu, Wenzhi; Liu, Mengying; et al. (Frontiers in Bioengineering and Biotechnology, 2024)
Extensive trauma disrupts endometrial regeneration by diminishing endometrial stem or progenitor cells. Endometrial epithelial organoids (EEOs) are used for endometrial regeneration. However, how EEOs repair injured endometrial tissues and their advantages over bone marrow mesenchymal stem cells (BMSCs) are unclear. This study explored whether EEOs surpass BMSCs to repair injured endometrium and examined whether endometrial restoration involves integrating EEOs into the endometrial tissue of the recipient. Rat EEOs (rEEOs) mimicking the features of the rat endometrium were developed. An endometrial injury rat model was used to compare the effects of rEEOs and rat BMSCs (rBMSCs) on endometrial regeneration and reproductive recovery. Bulk RNAsequencing analysis was conducted to investigate the capacity of rEEOs for endometrial regeneration and identify discrepancies between rEEOs and rBMSCs. Green fluorescent protein (GFP)-labeled rEEOs or red fluorescent protein-labeled rBMSCs were transplanted to track the transplanted cells in vivo. Fertility recovery in rats transplanted with rEEOs was more comparable to that of normal rats than in rBMSC-treated rats. rEEOs had a high concentration of endometrial epithelial stem or progenitor cells and secreted vascular endothelial growth factor-A to promote endometrial neovascularization. Cells from GFP-labeled rEEOs integrated and differentiated into functional glands within the injured endometrium. Transplanting EEOs restored the morphology and function of severe endometrial injury better than BMSC transplantation. EEO cells repair the endometrium by differentiating into functional glandular epithelial cells. These findings offer preclinical evidence supporting in vitro expansion and transplanting of EEOs as promising approaches to restore fertility in women with insufficient endometrial regeneration.